Fat infiltration in the lumbar multifidus and erector spinae muscles in subjects with sway-back posture - Pezolato, Adriano; de Vasconcelos, Everaldo Encide; Defino, Helton Luiz Aparecido; Nogueira-Barbosa, Marcello Henrique (European spine journal, 2012)
Aim Decreased activity of the lumbar stabilizer muscles has been identified in individuals with sway-back posture. Disuse can predispose these muscles to atrophy, which is characterized by a reduced cross-sectional area (CSA) and by fat infiltration. The aim of this study was to evaluate the amount of fat infiltration in the lumbar multifidus and lumbar erector spinae muscles as a sign of the muscle atrophy in individuals with sway-back posture, with and without low back pain. Materials and methods Forty-five sedentary individuals between 16 and 40 years old participated in this study. The sample was divided into three groups: symptomatic sway-back (SSBG) ( n = 15), asymptomatic sway-back (ASBG) ( n = 15), and control (CG) ( n = 15). The individuals were first subjected to photographic analysis to classify their postures and were then referred for a magnetic resonance imaging (MRI) examination of the lumbar spine. The total (TCSA) and functional (FCSA) cross-sectional areas of the lumbar erector spinae together with lumbar multifidus and isolated lumbar multifidus muscles were measured from L1 to S1. The amount of fat infiltration was estimated as the difference between the TCSA and the FCSA. Results Greater fat deposition was observed in the lumbar erector spinae and lumbar multifidus muscles of the individuals in the sway-back posture groups than in the control group. Pain may have contributed to the difference in the amount of fat observed in the groups with the same postural deviation. Similarly, sway-back posture may have contributed to the tissue substitution relative to the control group independently of low back pain. Conclusions The results of this study indicate that individuals with sway-back posture may be susceptible to morphological changes in their lumbar erector spinae and lumbar multifidus muscles, both due to the presence of pain and as a consequence of their habitual posture.